Pengelolaan Lingkungan dengan Pemanfaatan Air Hujan Menggunakan Teknik SODIS untuk Pemberdayaan Karang Taruna Gebangsari: Environmental Management by Utilizing Rainwater Using SODIS Techniques for the Empowerment of Gebangsari Taruna Corals - Filany, Devany England; Ulfah, Maria; Pranama, Hanasari Faida; Kurniawati, Septiana; Ardian, Via Valenta Kafita; Yuliani, Hana Eldiana (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Gebangsari Village is one of the villages in Genuk District, Semarang City, where when heavy rainfall often experiences floods. When there is rain, there is minimal access to clean water in Gebangsari Village, and people rely only on well water. Therefore, it is necessary to empower Karang Taruna Gebangsari to utilize rainwater with SODIS (Solar Water Disinfection) Technique to meet clean water needs during floods. The method used was interviews and observations with Gebangsari Village, the Community, and Gebangsari Village Taruna Corals. The program's implementation includes Socialization and Focus Group Discussion, Training, Mentoring, and Evaluation activities. This Community Service Program provides new knowledge and skills for the Gebangsari Village Community so that the community gets solutions to flood problems. The village also appreciated the impact of the SODIS Engineering community service program for helping the adequacy of clean water.